Physiological changes and shelf life of mango (Mangifera indica L.) Influenced by post harvest treatments (SAARC Journal of Agriculture, 2018)
The experiment examined the efficacy of various post harvest treatments namely control, hot water treatment, thin plastic film, chlorinated water, neem extract and garlic extract on shelf life and quality of mango. Parameters studied were colour, firmness, disease severity, disease incidence, total soluble solids, total weight loss, moisture content, dry matter and shelf life of mango. The longest shelf life of 15.41 days was found in mango fruits wrapped with thin plastic film.SAARC J. Agri., 15(2): 219-226 (2017)